Targeting visual-sensory and cognitive impairments following lateral ankle sprains: a practical framework for functional assessment across the return-to-sport continuum—Part 1. Sensory reweighting and cognitive impairments: what are we really talking about and why clinicians should consider central alterations in return to sport criteria - Picot, Brice; Maricot, Alexandre; Fourchet, François; Gokeler, Alli; Tassignon, Bruno; Lopes, Ronny; Hardy, Alexandre (Frontiers in Sports and Active Living, 2025)
Lateral ankle sprain (LAS) is the most common traumatic injury, with a high recurrence rate and chronic ankle instability (CAI) developing in ∼40% of cases. LAS leads to patho-mechanical, sensory-perceptual and motor-behavioral deficits. Poor management of the return-to-sport (RTS) is now considered a major cause of re-injury and development of CAI, particularly due to the lack of validated tests and the failure of existing ones to account for those central deficits. The first part of this topic aimed to clarify concepts of cognitive constructs and sensory reweighting and their association with CAI. We also aimed to identify objective RTS criteria and discuss their limits regarding their ability to encompass central impairments. Motor-cognitive deficits have been identified using computerized cognitive tasks and dual-task paradigms. More specifically, deficits in visual memory, processing speed or inhibitory control and attentional resource allocation have demonstrated reduced performance in CAI populations. In addition, altered sensory reweighting process towards visual input has also been observed. While objective criteria are crucial to prevent re-injury, current evaluations remain largely subjective and central impairments are unaccounted for in conventional RTS testing. The Ankle-GOTM score was recently developed to guide clinicians in decision making process. To date, it is the first validated score that could help to identify patients who will RTS at the same level, those at risk of recurrence and those who are more likely to become copers. Unfortunately, it does not target cognitive or sensory reweighting alterations, that are both relevant in sport to manage gameplay demands.